Esports in-game consumption across generations: Integrating motivated reasoning theory and the theory of planned behavior - Kun Chang; Jun-Phil Uhm; Hyun-Woo Lee (PLoS ONE, 2026)
The revenue from virtual non-functional products has become a significant revenue source for the video game industry. Despite growing interest, understanding the decision-making processes behind virtual non-functional products consumption in free-to-play games remains limited. This study contributes to existing literature by testing a multi-relational model (motivation-cognition-intention-behavior). We aim to examine how gamers’ self-presentation motivation is associated with their attitude, subjective norm, and perceived behavioral control, and how these factors relate to their purchase behavior. Data were collected via an online survey distributed on Reddit to esports gamers with prior purchase experience ( N = 239). All constructs were measured using established multi-item Likert scales. Structural equation modeling and multi-group analysis were conducted using Mplus 8.8. Results showed that gamers’ self-presentation motivation in the game is positively associated with gamers’ attitude ( β = .246, p < .001) and subjective norm ( β = .169, p < .05). Attitude ( β = .398, p < .001), subjective norm ( β = .155, p < .05), and perceived behavioral control ( β = .224, p < .001) were positively associated with purchase intention, which in turn predicted purchase behavior ( β = .600, p < .001). Further, we identified generational differences on the path of motivation-cognition-intention-behavior. The current study moves beyond a single-theory explanation by proposing a more holistic perspective of how gamers’ innate self-presentation motivations are associated with virtual non-functional products consumption. The findings revealed novel insights into generational differences in the decision-making processes, guiding tailored marketing strategies to boost virtual non-functional products consumption across segments.